Proletarische Virtuosen? Widersprüche und Verwerfungen in der Elitenpolitik der SED am Beispiel der Kampfgruppen der Arbeiterklasse - Siebeneichner, Tilmann (2013)
Abstract: "The members of the 'Combat Groups of the Working Class' were considered as proletarian virtuosos because they voluntarily spent their leisure time for their commitment to the protection of the 'Socialist achievements'. This way representing Communist resilience, they were supposed to be particularly honoured and recognized. Already in the 1950s, however, it became obvious that praising violence as a political maxim was widely perceived as contradicting other programmatic aspects of SED rule. Thus, an analysis of the Combat Groups looks promising for uncovering the inner contradictions of State Socialist rule - elite consciousness vs. egalitarianism, pacifism vs. militancy, spontaneity vs. 'ruling through' - and for understanding why it finally became a failure." (author's abstract)